COMPARISON OF ON-SITE TESTING WITH ONLINE TESTING DURING THE COVID-19 PANDEMIC - Stradiotová, Eva; Nemethova, Ildiko; Stefancik, Radoslav (Advanced Education, 2021)
In the paper, we deal with the comparison of the evaluation of students’ language skills in two environments, on-site and online. Testing took place through the moodle platform, where we used e-test, during the first and second waves of the pandemic. The main aim of the research was to find out what impact the environment in which the testing takes place has on the test results, i.e. in which environment students achieved better results. Printed tests were used for on-site testing. The on-site testing took place in the academic years 2018/2019 (summer term) and 2019/2020 (winter term). The online testing took place in the academic years 2019/2020 (summer term) and 2020/2021 (winter term). We compared the results of the testing, which took place in person at the university, with the results that the students achieved during the online testing. In the research of testing, we used the method of quantitative analysis and descriptive statistics, which allow us to better understand the correlation between the results obtained in on-site and online testing. Based on the data analysis, we confirmed the alternative hypothesis H1: Students who took part in on-site testing achieve better results than students who took part in online testing. Testing results show that students achieve better results in on-site testing than in online testing.